Intestinal Obstruction: Etiology and Complications in Patients Undergoing Surgery - Shah Hussain, Muhammad Ayaz, Hammad Zamir, Haider Ali, Shabab Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aimed to determine the causes and complications in patients undergoing surgical intervention for intestinal obstruction. Study Design: Prospective/Cross-sectional study Place and Duration: Department of surgery Lady Reading Hospital Peshawar from July 2022 to June 2023. Methodology: Total 110 patients of either gender presented with intestinal obstruction were included in this study. Detail demographics were recorded after taking informed written consent. Causes and postoperative complications were recorded. Data was analyzed by SPSS 23.0. Results: Mean age of patients was 42.48±12.54 years. 60 (54.55%) were males while 50 (45.45%) were females. Most commonly found causes of intestinal obstruction were adhesion in 35 (31.82%) followed by tuberculosis, rectal carcinoma and obstructed hernia in 24 (21.82%), 18 (16.36%), and 16 (14.55%) patients respectively. Postoperative complications were found in 12 (10.91%) patients, most common complication was wound infection in 5 (4.55%) patients followed by wound dehiscence in 3 (2.73%), 2 (1.82%) had burst abdomen and mortality found in 2 (1.82%). Conclusion: We concluded that the most commonly found causes of intestinal obstruction were adhesion, abdomen tuberculosis and rectal carcinoma. Most common complication was wound infection. Keywords: Intestinal Obstruction, Tuberculosis, Adhesion, Wound Infection, Mortality